New Insights in Addressing Cerebral Small Vessel Disease: Association With the Deep Medullary Veins - Xu, Zhihua; Li, Fangfei; Wang, Bing; Xing, Dengxiang; Pei, Yusong; Yang, Benqiang; Duan, Yang (Frontiers in Aging Neuroscience, 2020)
Objective To assess the suitability of deep medullary vein visibility in susceptibility weighted imaging—magnetic resonance imaging studies as a method for the diagnosis and evaluation of cerebral small vessel disease progression. Methods A total of 92 patients with CSVD were enrolled and baseline clinical and imaging data were reviewed retrospectively. Neuroimaging biomarkers of CSVD including high-grade white matter hyperintensity (HWMH), cerebral microbleed (CMB), enlarged perivascular space (PVS), and lacunar infarct (LI) were identified and CSVD burden was calculated. Cases were grouped accordingly as mild, moderate, or severe. The DMV was divided into six segments according to the regional anatomy. The total DMV score (0–18) was calculated as the sum of the six individual segmental scores, which ranged from 0 to 3, for a semi-quantitative assessment of the DMV based on segmental continuity and visibility. Results The DMV score was independently associated with the presence of HWMH, PVS, and LI (P < 0.05), but not with presence and absence of CMB (P > 0.05). Correlation between the DMV score and the CSVD burden was significant (P < 0.05) [OR 95% C.I., 1.227 (1.096–1.388)]. Conclusion The DMV score was associated with the presence and severity of CSVD.